2017
DOI: 10.15252/embr.201744822
|View full text |Cite
|
Sign up to set email alerts
|

Using CRISPR ‐based gene drive for agriculture pest control

Abstract: Response by the authors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…2A). For any induction times less than 10 h, the gene drive activity (18,19) remained below 50% (Fig. 3D).…”
Section: Percent Gene Drive Activitymentioning
confidence: 95%
See 3 more Smart Citations
“…2A). For any induction times less than 10 h, the gene drive activity (18,19) remained below 50% (Fig. 3D).…”
Section: Percent Gene Drive Activitymentioning
confidence: 95%
“…However, for isolates subjected to galactose induction (5 h), only the two PCRs corresponding to the gene drive allele (A, B) were present; reactions for the target allele were unable to amplify the expected fragment (C, D). A similar analysis was performed for eight clonal isolates from the NES strains (18,19). However, we sampled two isolates that were sensitive and two samples resistant to the SD-HIS condition; diagnostic PCRs illustrated that the target allele was still present for surviving colonies (Fig.…”
Section: Percent Gene Drive Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…This super-Mendelian genetic arrangement allows for the forced propagation of a genetic element within a population and has the potential to modify entire species on a global scale (BULL AND BARRICK 2017;GODFRAY et al 2017). Some of the possible benefits of this technology include eradication of invasive species (ESVELT AND GEMMELL 2017;PROWSE et al 2017), agricultural pest management (COURTIER-ORGOGOZO et al 2017), and elimination of insect-borne diseases such as malaria (GODFRAY et al 2017;LAMBERT et al 2018). A number of recent studies have demonstrated the potency and success of CRISPR-based gene drives in fungi (DICARLO et al 2015;ROGGENKAMP et al 2017;ROGGENKAMP et al 2018;SHAPIRO et al 2018), and metazoans (GANTZ et al 2015;HAMMOND et al 2016;CHAMPER et al 2017;GRUNWALD et al 2018).…”
Section: Introductionmentioning
confidence: 99%